P-v Criticality of a Specific Black Hole in f(R) Gravity Coupled with Yang-Mills Field. (25th June 2018) - Övgün, Ali
Abstract : We study the P - v criticality of a specific charged AdS type black hole (SBH) in f ( R ) gravity coupled with Yang-Mills field. In the extended phase space, we treat the cosmological constant as a thermodynamic pressure. After we study the various thermodynamical quantities, we show that the thermodynamic properties of the SBH behave as a Van der Waals liquid-gas system at the critical points and there is a first-order phase transition between small-large SBH.